207 Arrhythmia Inducibility in a Novel Normotensive Rodent Model of Arrhythmia is not Related to Connexin 43 Quantity and Phosphorylation States – Determining the Contribution of Hypertension and ageing on the Myocardial Substrate. (31st May 2014) - Zaman, Junaid; Patel, Pravina; Peters, Nicholas
Abstract : Introduction: Hypertension and ageing are the commonest risk factors for atrial fibrillation (AF) and a significant cause of ventricular dysfunction, which may lead to arrhythmia. Putative factors in the remodelled substrate are connexin 43 (Cx43), the most abundant cardiac gap junction and fibrosis. The spontaneous hypertensive rat (SHR) has been demonstrated to have increased AF compared to a normotensive control species (Wistar Kyoto). However, the exact substrate changes remain elusive, as is a normotensive model of naturally occurring cardiac arrhythmia. Methods: 40 Brown Norway (BN) and 40 SHR were aged simultaneously, with ex vivo Langendorff pacing protocols for atrial and ventricular arrhythmia performed at 3, 6, 9 and 12 months (n = 10 each group), which is the age at which SHRs develop spontaneous AF. Burst pacing was performed from right and left atria (RA/LA) from 150–30 ms in 10 ms decrements, then left ventricular (LV) apex extrastimulus pacing until ventricular effective refractory period was reached, or arrhythmia induced. Tissues were then divided and flash frozen for immunoblotting of Cx43. Electrophysiological data was recorded using a high-density microelectrode array placed on both RA and LA during atrial pacing and then RA and LV free wall during LV pacing. A subgroup (n = 4 each species) had non-invasive blood pressure recorded via tail-cuff plethysmography, echocardiography and implanted telemetry. Results: BN mean systolic pressure was significantly lower than SHR with a lower LV mass on echo and heart weight to body weight ratio (p < 0.05 at all ages). Both sets of animals demonstrated equal atrial and ventricular inducibility ex vivo at all timepoints between species (see Figure 1) and occurrence of spontaneous AF and atrial tachycardia (AT) on in vivo telemetry (see Figure 2). Total atrial connexin 43 levels were no different between species at any age or when subdivided into arrhythmia +/- groups. However, there was a decrease in total ventricular Cx43 in both species between the 3, vs 9 and 3 vs 12 month groups, with an increase in the percentage dephosphorylated (P0) fraction in younger animals, despite a lower percentage of ventricular arrhythmia than older animals of the same species. Conclusions: The novel findings of this study are as follows: 1. The Brown Norway rat is a novel small animal model of naturally occurring and provoked atria and ventricular arrhythmia, in addition to the recently described SHR. 2. The effects of age seem to be more potent on the arrhythmic substrate than hypertension. 3. The arrhythmia phenotype is not related to underlying Cx43 quantity or phosphorylation state. The mechanisms underlying the BN arrhythmia phenotype are undergoing continuing studies, specifically looking at fibrosis, Cx43 lateralisation and sodium channel expression.